Mycobiome associated with macadamia plants at different growth stages - Khan, Jahangir; Drenth, André; Akinsanmi, Olufemi A. (Frontiers in Agronomy, 2025)
Macadamia is a tree producing high-value nuts and is indigenous to subtropical Australia. Macadamia is commercially cultivated across the globe and the macadamia industry is experiencing increased crop losses caused by fungal pathogens. Limited information is available regarding the association of fungal microbes with macadamia nursery plants. Therefore, this study aims to characterise fungal microbes associated with macadamia plants across five growth stages in leaf, stem and root during four seasons. The fungal community in macadamia nursery plants was analysed using a culture-based approach. Fungi were isolated from germinated seedlings, 3-month-old seedlings, non-grafted plants, grafted trees and 2-year-old trees in orchard. A total of 63 fungal species were identified using DNA sequencing, mainly in the phylum Ascomycota, from the different plant organs. The fungal community structure was significantly influenced by the growth stages (P = 0.001) and plant organs (P<0.001). There was no significant seasonal (P = 0.021) effect in the number of fungal genera isolated from the plants. Grafted plants and young orchards had the richest fungal composition and diversity of the 63 fungal species. Alternaria, Arcopilus, Epicoccum, Nigrospora, and Preussia were found in the leaf, Nectria in the stem, and Mortierella and Penicillium in the root organ only. Diaporthe, Neopestalotiopsis, Pestalotiopsis, Fusarium, and Phyllosticta were detected in all three organs. This study revealed that fungal community richness and diversity in macadamia plants depend on the growth stage and organ examined.